MATEMATIKA DALAM ARSITEKTUR: KONSEP SUSUNAN BILANGAN REAL DALAM KONSTRUKSI ATAP LOPO DI BENTENG NONE - Apridus Lapenangga; Yohana Rowa; Meryani Lakapu (ATRIUM: Jurnal Arsitektur, 2020)
Title: Mathematics in Architecture: The Concept of Numbers in Roof Structure Construction of Fort None Lopo Fort None is a traditional fortress in which there are traditional buildings of the Dawan people, namely Lopo and Ume Kbubu. One of the Lopo in this area was once burned and has not been rebuilt. This is one of the reasons this study was conducted, to find out the mathematical elements in Lopo construction which can be useful as a design guidelines for other Lopo building construction. This study aims to analyze in depth the concept of configuration of real numbers on the Lopo roof construction in Benteng None, so the method used is qualitative research with ethnographic design. This discussion is carried out by analyzing three construction elements on the Lopo roof, namely: 5 inner circles, 26 outer circles and rectangles on the Lopo roof. So, it can be concluded that some construction elements on the Lopo roof which are mathematically analyzed show the existence of the concept of real number configuration. From this discussion, the results show that there are types of real number configuration, including: Monotonic real numbers descending, finite real numbers, fixed real numbers with fixed differences and real numbers with non-fixed differences.